Studi Parametrik Pengaruh Variasi Pengekangan Terhadap Nilai Kapasitas dan Daktilitas Penampang Kolom Beton Bertulang Bentuk T - Adveni H.A Lada; Partogi H. Simatupang; Andi H. Rizal (Universitas Nusa Cendana, 2021)
Column has a function as a successor of the entire building load for foundation with a cross-sectional shape which generally a square. In its development, the shape of column section has begun to vary, namely the 'L', 'T' and 'Plus (+)' shaped sections. The purpose of this study was to determine the effect of restraint parameters such as diameter of stirrups, distance between stirrups, diameter and configuration of longitudinal reinforcement also concrete quality on the capacity and ductility of T-shaped non-square column using Response-2000, XTRACT and SAP2000 programs to ensure the percentage comparison of the analysis result data is not more than 5%. The results of this study for each type of cross-section, namely each increase in the percentage of concrete quality parameters ranging from 25-35 MPa, the diameter of longitudinal reinforcement and diameter of stirrups will increase the value of capacity and decrease the value of ductility, while for each increase in the percentage of parameters the distance between stirrups will decrease the value of capacity and the ductility value. Meanwhile, the variation of longitudinal reinforcement configuration produces T2-1 section as cross section with the largest capacity value and T1-2 section as cross section with the greatest ductility value.